Clozapine: A Scientific Analysis of Global Publications during 1970-2021 - Grover, Sandeep; Gupta, B.M.; Ahmed, K.K. Mueen; Singh, Yogindra (International Journal of Pharmaceutical Investigation)
Aim: This study evaluates the research output on Clozapine included in Scopus database during 1970-2021. Materials and Methods: The quantitative and qualitative analysis of publications on “Clozapine” covered in Scopus database during 1970-2021 was undertaken. The results obtained were further analysed using additional features in Scopus database. Results: 7399 publications on “Clozapine” were obtained from Scopus international database and these publications received 189068 citations, averaging 25.55 citations per paper (CPP). There was initial rise in the number of publications per year from 1988 to 1995, after that the number of publications has remained relatively stable. Authors from USA, U.K. and Germany contributed to the largest number of publications (2136, 709 and 457 publications respectively), and publications with authors from USA, Canada and Germany registered the highest CPP and relative citation index (RCI). The authors from King’s College London, U.K, The Zucker Hillside Hospital, USA and University of Toronto, Canada published the highest number of publications. The organization that registered the highest CPP and RCI was Sandoz International GmbH, Switzerland, Long Island Jewish Medical Centre, USA and Vanderbilt University, School of Medicine, USA. The authors who published the highest number of publications were H.Y. Meltzer (USA), J.A. Lieberman (USA) and A. Weizman (Israel). The authors who registered the highest CPP and RCI were R.W. Kerwin (U.K.) and J.P. Lindermayer. The journals that published the highest number of publications were Journal of Clinical Psychopharmacology (351 papers), Journal of Clinical Psychiatry (282 papers), and American Journal of Psychiatry (255 papers). The most impactful publications were published in Archives of General Psychiatry, Schizophrenia Bulletin, Journal of Pharmacology and Experimental Therapeutics, and American Journal of Psychiatry. Conclusion: This study suggests that the numbers of publications on clozapine have remained stable over the years and maximum research has emerged from the developed countries.
Keywords: Clozapine; Atypical antipsychotics; Bibliometrics; Scientometrics.